PERSEPSI MAHASISWA TENTANG MATA KULIAH STATISTIK SERTA PENGARUHNYA TERHADAP PRESTASI BELAJAR STATISTIK MAHASISWA IKIP PGRI MADIUN - Sofia Nur Afifah; Ervan Johan Wicaksana (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
Students' perceptions of Statistics related to the their learning outcomes. Perception is the process of consciousness, namely the consciousness of an object which delivers to the understanding, the process or the ability to feel the results of knowledge and so obtained with a feeling and sense or intuition that is abstract. Perception will lead someone on giving meaning to the notion of something. Students' perceptions of subjects Statistics describes the level of students' knowledge and understanding of the statistics. The purposes of this study are: (1) determine the students' perception of on Statistics, (2) determine the influence of students' perception on Statistics. This study used the design of Mixed Methods, which consists of two types of research, the first one was qualitative research and another one was quantitative. The sample is taken from the students of fourth semester study program Primary Age Students Teachers' Training IKIP PGRI Madiun in the Academic Year of 2013/2014 consists of 28 students. Data collection techniques used are questionnaires and documentation. Data analysis techniques in this study used a qualitative descriptive technique. In addition to these techniques are also used in the form of a hypothesis test Spearman test.Based on the results the following results: (1) Students' Perceptions of Statistics Course outlines included into good category; (2) There is no influence of students' perceptions in statistics course. It is evident in the results or the value of P = 0.124 (P > 0.05) and the value of r xy = 0.294, which means the relationship between students' perceptions about Statistical study and the learning achievement is weak.